2012
DOI: 10.1111/j.1468-005x.2012.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards unions 2.0: rethinking the audience of social media engagement

Abstract: This paper aims to examine how trade union members perceive opportunities for online engagement and what the differences are between traditional and online audiences. The empirical work is based on a survey of members of a Greek union in the banking sector. The findings outline the characteristics of an audience that is likely to support information sharing and networking activities on the web. For this audience, traditional levels of loyalty and union participation were not strongly related with perceptions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 45 publications
0
64
2
7
Order By: Relevance
“…For example, social media in the workplace, in the context of union activities and beyond, have important implications that merit attention (Bucher et al 2013;Panagiotopoulos 2012). industrial disputes, law advice and employment) and when, where and with whom social media can be used to engage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, social media in the workplace, in the context of union activities and beyond, have important implications that merit attention (Bucher et al 2013;Panagiotopoulos 2012). industrial disputes, law advice and employment) and when, where and with whom social media can be used to engage.…”
Section: Discussionmentioning
confidence: 99%
“…Not only are these services offered by Internetbased organizations but also via online networking between professionals on an ad hoc basis. A study with union members in the Greek banking sector showed that Internet experiences could explain to a large extent the members' attitudes towards online engagement even irrespective of union loyalty indicators (Panagiotopoulos 2012). Workers use social media and their networking features to voice concerns about issues of working life, connect with colleagues and selforganize.…”
Section: Background: Ict In Union Communicationsmentioning
confidence: 99%
“…First, the relationship between traditional and social media audiences can be complicated for organisations (e.g., Kidd, 2011;Panagiotopoulos, 2012). Second, social media host distributed audiences that form around events or interests usually on an ad hoc basis (Highfield, Harrington, & Bruns, 2013).…”
Section: Social Media Engagement and The Challenge Of Responsivenessmentioning
confidence: 99%
“…Is this going to turn into a union thing?'" Beyond these studies, scholars have examined other digital communication channels, like how employees communicate via websites (Fitzgerald, Hardy, and Lucio 2012), e-forums (Greene, Hogan, and Grieco 2003;Robinson 2006), employee association websites (Heckscher and Carr e 2006), union websites (Panagiotopoulos and Barnett 2015), message boards (Saundry, Stewart, and Antcliff 2012), "friending" activity (Heckscher and McCarthy 2014), and how unions use social media (Panagiotopoulos 2012). (Turkopticon is not a labor union and was not founded with formal unionization in mind.)…”
Section: Conceptual Frameworkmentioning
confidence: 99%